Embedded copper plate manufacturing process
By using specific browning liquid and heat-resistant curing agent in the buried copper plate manufacturing process, the problems of poor browning effect of copper blocks and insufficient heat resistance of epoxy resin are solved, and the high stability of buried copper plates and Intensity reduces the phenomenon of explosive boards.
Patent Information
- Application Number
- CN202411552439.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
AI Technical Summary
In the existing buried copper plate manufacturing process, the copper block browning effect is poor, and the heat resistance and curing speed of the epoxy resin are insufficient, resulting in insufficient stability and strength of the buried copper plate, which is prone to explosive plates.
The copper block is browned with a specific browning liquid, including the use of 3-trifluoroacetoxypropyltrimethoxysilane and other components to enhance the browning effect of the copper block. At the same time, a heat-resistant curing agent and a composite enhanced defoaming agent were used to prepare an epoxy resin with strong heat resistance and a small number of bubbles after curing.
It effectively enhances the browning effect of the copper block, the heat resistance and curing speed of the epoxy resin, improves the stability and strength of the buried copper plate, and reduces the occurrence of explosive plates.
Smart Images

Figure BDA0005115433850000051 
Figure BDA0005115433850000061 
Figure BDA0005115433850000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of PCB buried copper plates, and in particular relates to a manufacturing process of buried copper plates. Background Art
[0002] As high-power electronic components such as high-frequency radio frequency (RF) and power amplifier (PA) have higher and higher requirements for PCB heat dissipation capabilities, the industry has begun to introduce a manufacturing process of embedding copper blocks inside printed circuit boards, which is called embedded copper boards. The purpose of this technology is to improve the heat dissipation performance of PCBs while saving the cost of high-frequency materials. The main process of the technology is to bury the copper block in a pre-opened groove in the board, and then fill the gap between the copper block and the board with resin by plugging the hole, so that the copper block and the PCB board are bonded into a whole.
[0003] Among them, the browning treatment of copper blocks is an extremely important step, which has two main purposes. One is to increase the specific surface area of the bonding surface, and the other is to form a layer of organic metal conversion film. This organic metal conversion film can enhance the bonding strength with the epoxy resin, and at the same time prevent the copper from being further corroded, enhance the acid resistance of copper, and ensure the quality and performance of PCB multilayer boards. However, the corrosion inhibitors in the browning liquid are generally N, O, S heterocyclic triazole compounds. These compounds can form covalent bonds and coordination bonds with the copper surface to form a highly stable organic metal film, which can effectively enhance the corrosion inhibition performance of the copper surface and the bonding strength with the polymer material. However, the organic metal film formed is relatively simple and the film thickness is small. The generated film may cause the board to burst due to water absorption, so it needs to be pressed within the specified time.
[0004] Because PCB boards experience rapid temperature changes and reach relatively high temperatures during manufacturing and use, epoxy resins with good heat shock resistance are required as bonding materials to press PCB boards together. Amine curing agents cure quickly, but release a large amount of heat and easily generate a large number of bubbles in the epoxy resin, thereby reducing the performance of the epoxy resin. At the same time, the cured epoxy resin is brittle and has poor heat resistance. The epoxy resin cured with anhydride curing agents has better heat resistance, but its curing speed is slow and the cured epoxy resin is also brittle. Summary of the invention
[0005] The purpose of the present invention is to provide a buried copper plate manufacturing process.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention comprises the following steps:
[0007] A copper buried plate manufacturing process, the specific preparation steps are:
[0008] The substrate material is cut into a substrate, and then a reference hole and a copper block groove are made on the substrate. The copper block is buried in the copper block groove and fixed. Then, the heat-resistant epoxy resin is filled into the gap between the copper block and the substrate. Then, a mechanical drilling is performed on the substrate to make a through hole, and a copper deposition process, a board electrical process and a pattern electrical process are performed in sequence. Then, a heat-resistant epoxy resin is used for secondary hole plugging and a secondary copper deposition process is performed. After the outer layer circuit is made, a secondary pattern electrical process is performed. Then, the outer layer of the PCB board is etched. After etching, the PCB board is tested for soldering conditions. After the test is completed, the PCB board is pressed and the excess glue layer of the PCB board is removed. After product testing, the product is obtained.
[0009] The copper block also includes browning treatment, and the specific steps are:
[0010] First, the copper block is washed twice with a sodium hydroxide solution of 1 mol / L concentration, and then the copper block is washed with deionized water until it is neutral, and the copper block is placed in a pre-impregnation solution for 30 to 40 seconds, and then the copper block is sprayed with a browning solution at 30 to 36°C for 60 to 70 seconds, and then the copper block is washed twice with deionized water, and then dried to obtain the copper block;
[0011] The pre-soak is prepared by adding 20 to 24 parts by mass of benzylsulfonamide and 1.6 to 2 parts by mass of tetrahydrofuran into 86 to 90 parts by mass of deionized water and stirring evenly.
[0012] Among them, the browning liquid is specifically:
[0013] First, 5 to 7 parts by mass of 3-trifluoroacetoxypropyltrimethoxysilane are added to 95 to 105 parts by mass of deionized water, and then 90 to 95 parts by mass of 25% sulfuric acid is added, and then 3 to 4 parts by mass of water-soluble methoxylated polyethylene glycol, 0.04 to 0.06 parts by mass of sodium chloride, 0.1 to 0.2 parts by mass of copper sulfate and 1 to 2 parts by mass of 50% hydrogen peroxide solution are added in sequence, and the mixture is stirred evenly to obtain the product.
[0014] Among them, the heat-resistant epoxy resin is specifically:
[0015] 95-105 parts by mass of bisphenol A epoxy resin and 20-22 parts by mass of octyl glycidyl ether are mixed and stirred evenly, then 20-30 parts by mass of alumina filler and 0.1-0.2 parts by mass of composite enhanced defoamer are added and mixed and stirred evenly, and finally 8-10 parts of heat-resistant curing agent are added and the temperature is raised to 70-80° C. and stirred evenly to obtain a heat-resistant epoxy resin;
[0016] Among them, the heat-resistant curing agent is specifically:
[0017] Tung oil and glycerol are mixed in a mass ratio of 1:0.4-0.5, and sodium hydroxide is added at a mass ratio of 0.3%-0.5% of the mass of the tung oil. The mixture is heated to 165-175° C. under nitrogen protection for reaction for 190-200 minutes, cooled to room temperature, and then allowed to stand for separation to obtain an organic phase a, and then the organic phase a is washed three times with an aqueous sodium chloride solution having a mass concentration of 8%-10%, and an excess of anhydrous magnesium sulfate is added for drying to obtain a product a after drying;
[0018] The product a and 3-hydroxy-3-methylglutaric anhydride are mixed in a mass ratio of 1:1.2-1.3, heated to 125-135°C under nitrogen protection for reaction for 200-210 minutes, slowly cooled to 90-95°C, maleic anhydride in an amount of 60%-70% of the mass of the product a is added, and the reaction is continued with stirring for 125-135 minutes. After the reaction is completed, an excess of ethyl acetate is added for extraction and separation to obtain an organic phase b, and then the organic phase a is washed three times with an aqueous sodium chloride solution having a mass concentration of 8%-10%, and an excess of anhydrous magnesium sulfate is added for drying. After drying, the ethyl acetate is removed by rotary evaporation at 35°C and 0.03MPa to obtain a heat-resistant curing agent;
[0019] Among them, the composite enhanced defoamer is specifically:
[0020] The obtained product is prepared by uniformly mixing 9 to 11 parts by mass of hydroxyl-terminated trifluoropropyl methyl silicone oil and 3 to 5 parts by mass of polyoxyethylene polyoxypropylene glycerol stearate.
[0021] Among them, copper plating treatment is to plate a layer of copper on the through-holes on the PCB board, board electroplating treatment is to plate a layer of copper on the entire board surface and hole walls, and graphic electroplating treatment is to use electroplating to plate the outer layer with secondary copper.
[0022] The beneficial effects of the present invention are:
[0023] (1) The present invention uses a specific browning liquid to brown the copper block, which effectively enhances the browning effect of the copper block. At the same time, a heat-resistant curing agent and a composite enhanced defoaming agent are used as components of the epoxy resin to prepare an epoxy resin with strong heat resistance and a small number of bubbles after curing, thereby enhancing the stability and strength of the buried copper plate;
[0024] (2) The present invention enhances the browning effect by using a corrosion inhibitor as a browning agent component. Conventional corrosion inhibitors such as benzotriazole form a relatively simple organic metal film with a small film thickness, resulting in a poor browning effect. Compared with benzotriazole, 3-trifluoroacetoxypropyltrimethoxysilane can form a multilayer composite browning film, thereby enhancing the browning effect. At the same time, it has a strong adsorption force with the copper surface, thereby enhancing the adhesion strength of the composite browning film. At the same time, it can also enhance the hydrophobicity and chemical resistance of the browning film, reduce the water absorption of the browning film, and enhance its stability, thereby reducing the explosion of the buried copper plate;
[0025] (3) The present invention enhances the heat resistance of epoxy resin glue by using a heat-resistant curing agent. Compared with conventional heat-resistant curing agents such as methyl hexahydrophthalic anhydride, the heat-resistant curing agent can effectively enhance the heat resistance of epoxy resin glue and the flexibility of epoxy resin, thereby enhancing the heat shock resistance of the buried copper plate. At the same time, the curing speed is faster and the curing time is shorter, which can improve the efficiency of the curing process;
[0026] (4) When epoxy resin is cured, bubbles are generated due to heat release. At the same time, the use of a heat-resistant curing agent with a faster curing speed will make the epoxy resin curing reaction more intense, thereby releasing heat faster and generating more bubbles. These bubbles will affect the subsequent strength and heat dissipation effect of the buried copper plate. Therefore, a defoaming agent needs to be added to reduce the number of bubbles in the epoxy resin. However, conventional defoaming agents have poor heat resistance and poor defoaming effect when used for epoxy resin curing. At the same time, a single defoaming agent is not effective. Therefore, the defoaming agent generally needs to be compounded. The present invention uses a compounded defoaming agent to reduce the number of bubbles in the epoxy resin. Compared with the conventional defoaming agent polydimethylsiloxane, the hydroxyl-terminated trifluoropropyl methyl silicone oil has excellent defoaming and anti-foaming properties and is more stable. At the same time, it has better compatibility with other types of defoaming agents and a better compounding effect.
[0027] (5) Polyoxyethylene polyoxypropylene glyceryl stearate is also a defoaming agent with high surface activity and strong antifoaming ability. At the same time, it has strong dispersibility and can enhance the dispersibility of hydroxyl-terminated trifluoropropyl methyl silicone oil in epoxy resin. It has a good synergistic effect with hydroxyl-terminated trifluoropropyl methyl silicone oil. DETAILED DESCRIPTION
[0028] The present invention will be further described in detail below in conjunction with the embodiments.
[0029] Example 1
[0030] 22 parts by mass of benzoylsulfonamide and 1.8 parts by mass of tetrahydrofuran were added into 88 parts by mass of deionized water, and the mixture was stirred evenly to obtain a pre-dip solution.
[0031] First, 6 parts by mass of 3-trifluoroacetoxypropyltrimethoxysilane are added to 100 parts by mass of deionized water, followed by adding 93 parts by mass of 25% sulfuric acid, and then successively adding 3.5 parts by mass of water-soluble methoxylated polyethylene glycol, 0.05 parts by mass of sodium chloride, 0.15 parts by mass of copper sulfate and 1.5 parts by mass of 50% hydrogen peroxide solution, and stirring evenly to obtain a brown liquid.
[0032] First, wash the copper block twice with a 1 mol / L sodium hydroxide solution, then wash the copper block with deionized water until it is neutral, place the copper block in the pre-impregnation solution for 35 seconds, then spray the copper block with a 33°C browning solution for 65 seconds, then wash the copper block twice with deionized water, and dry it to obtain the browning copper block.
[0033] Example 2
[0034] 20 parts by mass of benzylsulfonamide and 2 parts by mass of tetrahydrofuran were added into 86 parts by mass of deionized water, and the mixture was stirred evenly to obtain a pre-dip solution.
[0035] First, 7 parts by mass of 3-trifluoroacetoxypropyltrimethoxysilane are added to 105 parts by mass of deionized water, followed by adding 90 parts by mass of 25% sulfuric acid, and then successively adding 3 parts by mass of water-soluble methoxylated polyethylene glycol, 0.06 parts by mass of sodium chloride, 0.1 parts by mass of copper sulfate and 1 part by mass of 50% by mass of hydrogen peroxide solution, and stirring evenly to obtain a brown liquid.
[0036] First, wash the copper block twice with a 1 mol / L sodium hydroxide solution, then wash the copper block with deionized water until it is neutral, place the copper block in the pre-impregnation solution for 30 seconds, then spray the copper block with a 30°C browning solution for 70 seconds, then wash the copper block twice with deionized water, and dry it to obtain the browned copper block.
[0037] Example 3
[0038] 24 parts by mass of benzylsulfonamide and 1.6 parts by mass of tetrahydrofuran were added into 90 parts by mass of deionized water, and stirred evenly to obtain a pre-dip solution.
[0039] First, 5 parts by mass of 3-trifluoroacetoxypropyltrimethoxysilane are added to 95 parts by mass of deionized water, followed by adding 95 parts by mass of 25% sulfuric acid, and then successively adding 4 parts by mass of water-soluble methoxylated polyethylene glycol, 0.04 parts by mass of sodium chloride, 0.2 parts by mass of copper sulfate and 2 parts by mass of 50% by mass of hydrogen peroxide solution, and stirring evenly to obtain a browning liquid.
[0040] First, wash the copper block twice with a 1 mol / L sodium hydroxide solution, then wash the copper block with deionized water until it is neutral, place the copper block in the pre-impregnation solution for 40 seconds, then spray the copper block with a 36°C browning solution for 60 seconds, then wash the copper block twice with deionized water, and dry it to obtain the browning copper block.
[0041] Example 4
[0042] First, 6 parts by mass of benzotriazole are added to 100 parts by mass of deionized water, followed by adding 93 parts by mass of 25% sulfuric acid, and then adding 3.5 parts by mass of water-soluble methoxylated polyethylene glycol, 0.05 parts by mass of sodium chloride, 0.15 parts by mass of copper sulfate and 1.5 parts by mass of 50% by mass of hydrogen peroxide solution in sequence, and stirring evenly to obtain a brown liquid.
[0043] The rest is the same as in Example 1.
[0044] Example 5
[0045] First, 6 parts by mass of 3-trifluoroacetoxypropyltrimethoxysilane are added to 100 parts by mass of deionized water, followed by adding 93 parts by mass of 10% sulfuric acid, and then successively adding 3.5 parts by mass of water-soluble methoxylated polyethylene glycol, 0.05 parts by mass of sodium chloride, 0.15 parts by mass of copper sulfate and 1.5 parts by mass of 50% hydrogen peroxide solution, and stirring evenly to obtain a browning liquid.
[0046] The rest is the same as in Example 1.
[0047] Example 6
[0048] First, 6 parts by mass of 3-trifluoroacetoxypropyltrimethoxysilane are added to 100 parts by mass of deionized water, followed by adding 93 parts by mass of 25% sulfuric acid, and then successively adding 3.5 parts by mass of water-soluble methoxylated polyethylene glycol, 0.05 parts by mass of sodium chloride, 0.15 parts by mass of copper sulfate and 1.5 parts by mass of 20% by mass of hydrogen peroxide solution, and stirring evenly to obtain a brown liquid.
[0049] The rest is the same as in Example 1.
[0050] Example 7
[0051] First, wash the copper block twice with a 0.2 mol / L sodium hydroxide solution, then wash the copper block with deionized water until it is neutral, place the copper block in the pre-impregnation solution for 35 seconds, then spray the copper block with a 33°C browning solution for 65 seconds, then wash the copper block twice with deionized water, and dry it to obtain the browning copper block.
[0052] The rest is the same as in Example 1.
[0053] Example 8
[0054] First, wash the copper block twice with a 1 mol / L sodium hydroxide solution, then wash the copper block with deionized water until it is neutral, place the copper block in the pre-impregnation solution for 15 seconds, then spray the copper block with a 33°C browning solution for 65 seconds, then wash the copper block twice with deionized water, and dry it to obtain the browning copper block.
[0055] The rest is the same as in Example 1.
[0056] Example 9
[0057] First, wash the copper block twice with a 1 mol / L sodium hydroxide solution, then wash the copper block with deionized water until it is neutral, place the copper block in the pre-impregnation solution for 35 seconds, then spray the copper block with a 45°C browning solution for 65 seconds, then wash the copper block twice with deionized water, and dry it to obtain the browned copper block.
[0058] The rest is the same as in Example 1.
[0059] Test 1:
[0060] The anti-peeling bonding strength of the browned copper blocks prepared in some Examples 1 to 9 was measured. At the same time, the browned copper blocks prepared in some Examples 1 to 9 were placed in a 10% HCl environment for 1 hour to observe whether pink circles would appear on the browned copper blocks. The specific data are shown in Table 1.
[0061] Table 1 Performance data of brown copper block
[0062]
[0063]
[0064] It can be seen from Table 1 that the browned copper blocks prepared in Examples 1 to 3 have the highest anti-peeling bonding strength and no pink circle phenomenon occurs, indicating that the browned film has the best performance; the reason why the data in Example 4 is not as good as that in Example 1 may be that after 3-trifluoroacetoxypropyltrimethoxysilane is replaced with benzotriazole, the browned film formed is relatively simple, so its performance is worse; the reason why the data in Example 5 is not as good as that in Example 1 may be that the mass concentration of sulfuric acid is low, and 3-trifluoroacetoxypropyltrimethoxysilane is not completely hydrolyzed, which affects the subsequent browning reaction; the reason why the data in Example 6 is not as good as that in Example 1 may be that the concentration of hydrogen peroxide is low, and the etching effect of the copper surface is not good, which affects the browning effect; the reason why the data in Example 7 is not as good as that in Example 1 may be that the concentration of the sodium hydroxide solution for washing the copper block is low, and the impurities on the surface of the copper block are not completely removed, which affects the subsequent browning effect; the reason why the data in Example 8 is not as good as that in Example 1 may be that the pre-immersion time of the copper block is short, and the surface of the copper block is not completely activated, which affects the subsequent browning effect; the reason why the data in Example 9 is not as good as that in Example 1 may be that the temperature of the browning liquid is high, on the one hand, the copper surface will be over-etched, and on the other hand, the hydrogen peroxide will decompose, thereby affecting the browning effect.
[0065] The browned copper block prepared in Example 1 was further used in Examples 10 to 21 to prepare buried copper plates.
[0066] Example 10
[0067] Tung oil and glycerol were mixed in a mass ratio of 1:0.45, and sodium hydroxide (0.4% by mass of the tung oil) was added at the same time, and the mixture was heated to 170° C. under nitrogen protection for reaction for 195 min, and then cooled to room temperature and allowed to stand for separation to obtain an organic phase a, and then the organic phase a was washed three times with a 9% mass concentration sodium chloride aqueous solution, and then dried with excess anhydrous magnesium sulfate to obtain a product a after drying;
[0068] The product a and 3-hydroxy-3-methylglutaric anhydride were mixed in a mass ratio of 1:1.25, heated to 130°C under nitrogen protection for reaction for 205 minutes, slowly cooled to 93°C, and maleic anhydride in an amount of 65% by mass of the product a was added, and the reaction was continued with stirring for 130 minutes. After the reaction was completed, excess ethyl acetate was added for extraction and separation to obtain an organic phase b, and then the organic phase a was washed three times with a 9% mass concentration sodium chloride aqueous solution, and excess anhydrous magnesium sulfate was added for drying. After drying, the ethyl acetate was removed by rotary evaporation at 35°C and 0.03MPa to obtain a heat-resistant curing agent.
[0069] The composite enhanced defoamer is obtained by uniformly mixing 10 parts by mass of hydroxyl-terminated trifluoropropyl methyl silicone oil and 4 parts by mass of polyoxyethylene polyoxypropylene glycerol stearate.
[0070] 100 parts by mass of bisphenol A epoxy resin and 21 parts by mass of octyl glycidyl ether are mixed and stirred evenly, then 25 parts by mass of alumina filler and 0.15 parts by mass of composite enhanced defoamer are added and mixed and stirred evenly, finally 9 parts of heat-resistant curing agent are added and the temperature is raised to 75°C and stirred evenly to obtain a heat-resistant epoxy resin.
[0071] The substrate material is cut into a substrate, and then a reference hole and a copper block groove are made on the substrate. The browned copper block is buried in the copper block groove and fixed. Then, the heat-resistant epoxy resin is filled into the gap between the copper block and the substrate. Then, a mechanical drilling is performed on the substrate to make a through hole, and a copper deposition process, a board electrical process and a pattern electrical process are performed in sequence. Then, a heat-resistant epoxy resin is used for secondary plugging and a secondary copper deposition process is performed. After the outer layer circuit is made, a secondary pattern electrical process is performed. Then, the outer layer of the PCB board is etched. After the etching is completed, the soldering condition of the PCB board is tested. After the test is completed, the PCB board is pressed and the excess glue layer of the PCB board is removed. After the product inspection, the buried copper board is obtained.
[0072] Embodiment 11
[0073] Tung oil and glycerol were mixed in a mass ratio of 1:0.4, and sodium hydroxide (0.3% by mass of the tung oil) was added at the same time, and the mixture was heated to 175° C. under nitrogen protection for reaction for 190 min, and then cooled to room temperature and allowed to stand for separation to obtain an organic phase a, and then the organic phase a was washed three times with an 8% by mass sodium chloride aqueous solution, and then dried with excess anhydrous magnesium sulfate to obtain a product a after drying;
[0074] The product a and 3-hydroxy-3-methylglutaric anhydride were mixed in a mass ratio of 1:1.2, heated to 125°C under nitrogen protection for reaction for 210 minutes, slowly cooled to 90°C, and maleic anhydride in an amount of 70% by mass of the product a was added, and the reaction was continued with stirring for 125 minutes. After the reaction was completed, excess ethyl acetate was added for extraction and separation to obtain an organic phase b, and then the organic phase a was washed three times with an 8% mass concentration sodium chloride aqueous solution, and excess anhydrous magnesium sulfate was added for drying. After drying, the ethyl acetate was removed by rotary evaporation at 35°C and 0.03MPa to obtain a heat-resistant curing agent.
[0075] The composite enhanced defoamer is obtained by uniformly mixing 9 parts by mass of hydroxyl-terminated trifluoropropyl methyl silicone oil and 5 parts by mass of polyoxyethylene polyoxypropylene glycerol stearate.
[0076] 95 parts by mass of bisphenol A epoxy resin and 22 parts by mass of octyl glycidyl ether were mixed and stirred evenly, and then 20 parts by mass of alumina filler and 0.2 parts by mass of composite enhanced defoaming agent were added and mixed and stirred evenly, and finally 10 parts of heat-resistant curing agent were added and the temperature was raised to 70°C and stirred evenly to obtain a heat-resistant epoxy resin.
[0077] The substrate material is cut into a substrate, and then a reference hole and a copper block groove are made on the substrate. The browned copper block is buried in the copper block groove and fixed. Then, the heat-resistant epoxy resin is filled into the gap between the copper block and the substrate. Then, a mechanical drilling is performed on the substrate to make a through hole, and a copper deposition process, a board electrical process and a pattern electrical process are performed in sequence. Then, a heat-resistant epoxy resin is used for secondary plugging and a secondary copper deposition process is performed. After the outer layer circuit is made, a secondary pattern electrical process is performed. Then, the outer layer of the PCB board is etched. After the etching is completed, the soldering condition of the PCB board is tested. After the test is completed, the PCB board is pressed and the excess glue layer of the PCB board is removed. After the product inspection, the buried copper board is obtained.
[0078] Example 12
[0079] Tung oil and glycerol were mixed in a mass ratio of 1:0.5, and sodium hydroxide (0.5% by mass of the tung oil) was added at the same time, and the temperature was raised to 165° C. under nitrogen protection for reaction for 200 min, and the mixture was cooled to room temperature and allowed to stand for separation to obtain an organic phase a, and then the organic phase a was washed three times with a 10% mass concentration sodium chloride aqueous solution, and an excess of anhydrous magnesium sulfate was added for drying to obtain a product a after drying;
[0080] The product a and 3-hydroxy-3-methylglutaric anhydride were mixed in a mass ratio of 1:1.3, heated to 135°C under nitrogen protection for reaction for 200 minutes, slowly cooled to 95°C, maleic anhydride in an amount of 60% by mass of the product a was added, and the reaction was continued with stirring for 135 minutes. After the reaction was completed, excess ethyl acetate was added for extraction and separation to obtain an organic phase b. Subsequently, the organic phase a was washed three times with a 10% mass concentration sodium chloride aqueous solution, and excess anhydrous magnesium sulfate was added for drying. After drying, the ethyl acetate was removed by rotary evaporation at 35°C and 0.03MPa to obtain a heat-resistant curing agent.
[0081] The composite enhanced defoamer is obtained by uniformly mixing 11 parts by mass of hydroxyl-terminated trifluoropropyl methyl silicone oil and 3 parts by mass of polyoxyethylene polyoxypropylene glycerol stearate.
[0082] 105 parts by mass of bisphenol A epoxy resin and 20 parts by mass of octyl glycidyl ether were mixed and stirred evenly, and then 30 parts by mass of alumina filler and 0.1 parts by mass of composite enhanced defoamer were added and mixed and stirred evenly, and finally 8 parts of heat-resistant curing agent were added and the temperature was raised to 80°C and stirred evenly to obtain a heat-resistant epoxy resin.
[0083] The substrate material is cut into a substrate, and then a reference hole and a copper block groove are made on the substrate. The browned copper block is buried in the copper block groove and fixed. Then, the heat-resistant epoxy resin is filled into the gap between the copper block and the substrate. Then, a mechanical drilling is performed on the substrate to make a through hole, and a copper deposition process, a board electrical process and a pattern electrical process are performed in sequence. Then, a heat-resistant epoxy resin is used for secondary plugging and a secondary copper deposition process is performed. After the outer layer circuit is made, a secondary pattern electrical process is performed. Then, the outer layer of the PCB board is etched. After the etching is completed, the soldering condition of the PCB board is tested. After the test is completed, the PCB board is pressed and the excess glue layer of the PCB board is removed. After the product inspection, the buried copper board is obtained.
[0084] Example 13
[0085] The heat-resistant curing agent in this embodiment is methyl hexahydrophthalic anhydride.
[0086] 100 parts by mass of bisphenol A epoxy resin and 21 parts by mass of octyl glycidyl ether are mixed and stirred evenly, then 25 parts by mass of alumina filler and 0.15 parts by mass of composite enhanced defoamer are added and mixed and stirred evenly, finally 9 parts of heat-resistant curing agent are added and the temperature is raised to 75°C and stirred evenly to obtain a heat-resistant epoxy resin.
[0087] The rest is the same as Example 10.
[0088] Embodiment 14
[0089] Tung oil and glycerol were mixed in a mass ratio of 1:0.45, and sodium hydroxide (0.4% by mass of the tung oil) was added at the same time, and the mixture was heated to 170° C. under nitrogen protection for reaction for 195 min, and then cooled to room temperature and allowed to stand for separation to obtain an organic phase a, and then the organic phase a was washed three times with a 9% mass concentration sodium chloride aqueous solution, and then dried with excess anhydrous magnesium sulfate to obtain a product a after drying;
[0090] The product a and succinic anhydride were mixed in a mass ratio of 1:1.25, heated to 130°C under nitrogen protection for reaction for 205 minutes, slowly cooled to 93°C, maleic anhydride in an amount of 65% by mass of the product a was added, and the reaction was continued with stirring for 130 minutes. After the reaction was completed, excess ethyl acetate was added for extraction and separation to obtain an organic phase b. Subsequently, the organic phase a was washed three times with a 9% mass concentration sodium chloride aqueous solution, and excess anhydrous magnesium sulfate was added for drying. After drying, the ethyl acetate was removed by rotary evaporation at 35°C and 0.03MPa to obtain a heat-resistant curing agent.
[0091] The rest is the same as Example 10.
[0092] Embodiment 15
[0093] Tung oil and glycerol were mixed in a mass ratio of 1:0.45, and sodium hydroxide (0.4% by mass of the tung oil) was added at the same time, and the temperature was raised to 170° C. for reaction for 195 min, and the mixture was cooled to room temperature and allowed to stand for separation to obtain an organic phase a, and then the organic phase a was washed three times with a 9% mass concentration sodium chloride aqueous solution, and an excess of anhydrous magnesium sulfate was added for drying to obtain a product a after drying;
[0094] The product a and 3-hydroxy-3-methylglutaric anhydride were mixed in a mass ratio of 1:1.25, the temperature was raised to 130°C for reaction for 205 minutes, the temperature was slowly lowered to 93°C, maleic anhydride in an amount of 65% by mass of the product a was added, and the reaction was continued with stirring for 130 minutes. After the reaction was completed, excess ethyl acetate was added for extraction and separation to obtain an organic phase b, and then the organic phase a was washed three times with a 9% mass concentration sodium chloride aqueous solution, and excess anhydrous magnesium sulfate was added for drying. After drying, the ethyl acetate was removed by rotary evaporation at 35°C and 0.03MPa to obtain a heat-resistant curing agent.
[0095] The rest is the same as Example 10.
[0096] Example 16
[0097] Tung oil and glycerol were mixed in a mass ratio of 1:0.45, and sodium hydroxide (0.4% by mass of the tung oil) was added at the same time, and the mixture was heated to 170° C. under nitrogen protection for reaction for 195 min, and then cooled to room temperature and allowed to stand for separation to obtain an organic phase a, and then the organic phase a was washed three times with a 3% mass concentration sodium chloride aqueous solution, and then dried with excess anhydrous magnesium sulfate to obtain a product a after drying;
[0098] The product a and 3-hydroxy-3-methylglutaric anhydride were mixed in a mass ratio of 1:1.25, heated to 130°C under nitrogen protection for reaction for 205 minutes, slowly cooled to 93°C, and maleic anhydride in an amount of 65% by mass of the product a was added, and the reaction was continued with stirring for 130 minutes. After the reaction was completed, excess ethyl acetate was added for extraction and separation to obtain an organic phase b, and then the organic phase a was washed three times with a 3% mass concentration sodium chloride aqueous solution, and excess anhydrous magnesium sulfate was added for drying. After drying, the ethyl acetate was removed by rotary evaporation at 35°C and 0.03MPa to obtain a heat-resistant curing agent.
[0099] The rest is the same as Example 10.
[0100] Embodiment 17
[0101] 100 parts by mass of bisphenol A epoxy resin and 21 parts by mass of octyl glycidyl ether are mixed and stirred evenly, then 25 parts by mass of alumina filler and 0.15 parts by mass of composite enhanced defoaming agent are added and mixed and stirred evenly, finally 5 parts of heat-resistant curing agent are added and the temperature is raised to 75°C and stirred evenly to obtain a heat-resistant epoxy resin.
[0102] The rest is the same as Example 10.
[0103] Embodiment 18
[0104] The composite enhanced defoamer is obtained by uniformly mixing 9 parts by mass of polydimethylsiloxane and 5 parts by mass of polyoxyethylene polyoxypropylene glycerol stearate.
[0105] The rest is the same as Example 11.
[0106] Embodiment 19
[0107] The composite enhanced defoamer is obtained by uniformly mixing 9 parts by mass of hydroxyl-terminated trifluoropropyl methyl silicone oil and 5 parts by mass of sucrose stearate.
[0108] The rest is the same as Example 11.
[0109] Embodiment 20
[0110] 95 parts by mass of bisphenol A epoxy resin and 22 parts by mass of octyl glycidyl ether were mixed and stirred evenly, and then 20 parts by mass of alumina filler and 0.05 parts by mass of composite enhanced defoaming agent were added and mixed and stirred evenly, and finally 10 parts of heat-resistant curing agent were added and the temperature was raised to 70°C and stirred evenly to obtain a heat-resistant epoxy resin.
[0111] The rest is the same as Example 11.
[0112] Embodiment 21
[0113] 95 parts by mass of bisphenol A epoxy resin, 22 parts by mass of octyl glycidyl ether, 20 parts by mass of alumina filler, 0.2 parts by mass of composite enhanced defoamer and 10 parts by mass of heat-resistant curing agent were mixed and stirred evenly, and the temperature was raised to 70° C. and stirred evenly to obtain a heat-resistant epoxy resin.
[0114] The rest is the same as Example 11.
[0115] Test 2:
[0116] The heat resistance of the buried copper plates prepared in Examples 10 to 21 was measured according to the IPC-TM650 2.6.8 method. According to the formula a=number of broken plates / total number of plates, b=number of bubble plates / total number of plates, the thermal conductivity c and peel strength d of the epoxy resin were also measured. The specific data are shown in Table 2.
[0117] Table 2 Performance data of buried copper plate and epoxy resin in Example 10 to Example 21
[0118]
[0119]
[0120] It can be seen from Table 2 that the copper-embedded plate and epoxy resin prepared in Examples 10 to 12 have the best performance data; the reason why the data in Example 13 is not as good as that in Example 10 may be that the heat-resistant curing agent is replaced with methylhexahydrophthalic anhydride. On the one hand, the heat resistance of epoxy resin is poorer because of methylhexahydrophthalic anhydride, and on the other hand, methylhexahydrophthalic anhydride cannot enhance the flexibility of epoxy resin, thereby enhancing the heat shock resistance of epoxy resin. The possibility of bubbles and fractures is greater, and at the same time, the thermal conductivity and peel strength of epoxy resin are also affected; the reason why the data in Example 14 is not as good as that in Example 10 may be that after 3-hydroxy-3-methylglutaric anhydride is replaced with succinic anhydride, the heat-resistant curing agent prepared has weaker heat resistance, and its compatibility and curing effect are also worse, which affects the subsequent curing process; the reason why the data in Example 15 is not as good as that in Example 10 may be that the reaction is not carried out under nitrogen protection, and more side reactions occur, which affects the performance of the heat-resistant curing agent; the reason why the data in Example 16 is not as good as that in Example 10 may be that the concentration of sodium chloride solution is low, The reaction product is more easily hydrolyzed when washed with water, thereby affecting the performance of the curing agent; the reason why the data in Example 17 is not as good as that in Example 10 may be that the amount of heat-resistant curing agent used is relatively small, so the curing effect is not good; the reason why the data in Example 18 is not as good as that in Example 11 may be that after the hydroxyl-terminated trifluoropropyl methyl silicone oil is replaced with polydimethylsiloxane, the stability and compatibility of polydimethylsiloxane are worse, and the compounding effect is not good, which affects the effect of the composite enhanced defoamer; the reason why the data in Example 19 is not as good as that in Example 11 may be that after polyoxyethylene polyoxypropylene glycerol stearate is replaced with sucrose stearate, on the one hand, its stability is worse and it is easy to deteriorate under high temperature conditions, and on the other hand, its dispersibility is weaker, and the synergistic effect with hydroxyl-terminated trifluoropropyl methyl silicone oil is weaker; the reason why the data in Example 20 is not as good as that in Example 11 may be that the amount of composite enhanced defoamer used is relatively low, so the defoaming effect is not good; the reason why the data in Example 21 is not as good as that in Example 11 may be that the materials are not stirred and mixed in steps, and the heat-resistant epoxy resin components are unevenly distributed, thereby affecting its curing effect and performance.
Claims
1. A copper buried plate manufacturing process, characterized in that: The specific preparation steps are: The substrate material is cut into a substrate, and then a reference hole and a copper block groove are made on the substrate. The copper block is buried in the copper block groove and fixed. Then, the heat-resistant epoxy resin is filled into the gap between the copper block and the substrate. Then, a mechanical drilling is performed on the substrate to make a through hole, and a copper deposition process, a board electrical process and a pattern electrical process are performed in sequence. Then, a heat-resistant epoxy resin is used for secondary hole plugging and a secondary copper deposition process is performed. After the outer layer circuit is made, a secondary pattern electrical process is performed. Then, the outer layer of the PCB board is etched. After etching, the PCB board is tested for soldering conditions. After the test is completed, the PCB board is pressed and the excess glue layer of the PCB board is removed. After product testing, the product is obtained.
2. A copper buried plate manufacturing process as claimed in claim 1, characterized in that: The copper block also includes browning treatment, the specific steps are: First, wash the copper block twice with a 1 mol / L sodium hydroxide solution, then wash the copper block with deionized water until it is neutral, place the copper block in the pre-impregnation solution for 30 to 40 seconds, then spray the copper block with a 30 to 36°C browning solution for 60 to 70 seconds, then wash the copper block twice with deionized water, and dry it.
3. A copper buried plate manufacturing process as claimed in claim 2, characterized in that: The pre-soak is specifically: Add 20 to 24 parts by mass of benzylsulfonamide and 1.6 to 2 parts by mass of tetrahydrofuran into 86 to 90 parts by mass of deionized water, and stir evenly to obtain the product.
4. A copper buried plate manufacturing process as claimed in claim 2, characterized in that: The specific browning liquid is: First, 5 to 7 parts by mass of 3-trifluoroacetoxypropyltrimethoxysilane are added to 95 to 105 parts by mass of deionized water, and then 90 to 95 parts by mass of 25% sulfuric acid is added, and then 3 to 4 parts by mass of water-soluble methoxylated polyethylene glycol, 0.04 to 0.06 parts by mass of sodium chloride, 0.1 to 0.2 parts by mass of copper sulfate and 1 to 2 parts by mass of 50% hydrogen peroxide solution are added in sequence, and the mixture is stirred evenly to obtain the product.
5. A copper buried plate manufacturing process as claimed in claim 1, characterized in that: The heat-resistant epoxy resin is specifically: 95-105 parts by mass of bisphenol A epoxy resin and 20-22 parts by mass of octyl glycidyl ether are mixed and stirred evenly, then 20-30 parts by mass of alumina filler and 0.1-0.2 parts by mass of composite enhanced defoamer are added and mixed and stirred evenly, finally 8-10 parts of heat-resistant curing agent are added and the temperature is raised to 70-80°C and stirred evenly to obtain the product.
6. A copper buried plate manufacturing process as claimed in claim 5, characterized in that: The heat-resistant curing agent is specifically: Tung oil and glycerol are mixed in a mass ratio of 1:0.4-0.5, and sodium hydroxide is added at a mass ratio of 0.3%-0.5% of the mass of the tung oil. The mixture is heated to 165-175° C. under nitrogen protection for reaction for 190-200 minutes, cooled to room temperature, and then allowed to stand for separation to obtain an organic phase a, and then the organic phase a is washed three times with an aqueous sodium chloride solution having a mass concentration of 8%-10%, and an excess of anhydrous magnesium sulfate is added for drying to obtain a product a after drying; The product a and 3-hydroxy-3-methylglutaric anhydride are mixed in a mass ratio of 1:1.2-1.3, and the temperature is raised to 125-135° C. under nitrogen protection for reaction for 200-210 min, and the temperature is slowly lowered to 90-95° C., and maleic anhydride in an amount of 60%-70% of the mass of the product a is added, and the stirring reaction is continued for 125-135 min. After the reaction is completed, excess ethyl acetate is added for extraction and separation to obtain an organic phase b, and then the organic phase a is washed three times with an aqueous sodium chloride solution with a mass concentration of 8%-10%, and excess anhydrous magnesium sulfate is added for drying. After drying, the ethyl acetate is removed by rotary evaporation at 35° C. and 0.03 MPa to obtain the product.
7. A copper buried plate manufacturing process as claimed in claim 5, characterized in that: The composite enhanced defoamer is specifically: The obtained product is prepared by uniformly mixing 9 to 11 parts by mass of hydroxyl-terminated trifluoropropyl methyl silicone oil and 3 to 5 parts by mass of polyoxyethylene polyoxypropylene glycerol stearate.
8. A copper buried plate manufacturing process as claimed in claim 1, characterized in that: The copper plating process is to plate a layer of copper on the through holes on the PCB board, the board electroplating process is to plate a layer of copper on the entire board surface and the hole wall, and the figure electroplating process is to use electroplating to plate a second layer of copper on the outer layer.